ESTIMASI AKTIVA DAN PASIVA SUMBERDAYA AIR DENGAN MODEL NERACA AIR DAN SISTEM INFORMASI GEOSPASIAL BERBASIS PENDEKATAN FISIOGRAFI DI KABUPATEN BLORA - Tommy Andryan Tivianton; Rifai Munajad; Sugeng Riyadi Wijanarko (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2013)
ABSTRACT Water is one of the most essential human needs. Meet the need for water becomes a serious problem, especially in areas with minimum water availability. Physiographic characteristics of structural folds in Blora only able to cover 37.9% of the population needs. Objectives to be achieved through this research was to determine the water balance of the potential availability of water resources and the need for total water covers the domestic sector, agriculture, fisheries, industry, and livestock. Measurement method is based on physiographic units using Geospatial Information System (GIS) that includes all of the availability of water by calculating the quantity of rain water areas, surface water, and groundwater are available. Availability of water that is then associated with the total water needs of all sectors in Blora. The result is a map of the distribution of water availability, water demand, and balance in Blora. Keyword : water balance, physiographic, GIS.